Entrepreneurial Education as a Tool for Personal and Professional Development in Vocational Training Centers in Mozambique - Francisco Leite, Atanásio; Gonçalves, Bruno Miguel Ferreira (Innovations in Pedagogy and Technology, 2025)
In a scenario characterized by rapid technological and economic changes, entrepreneurial education emerges as a fundamental tool for preparing students to become resilient and proactive professionals. This article explores the importance of entrepreneurial education in training individuals capable of facing the challenges of the modern job market. Through a mixed-methods approach combining qualitative interviews and quantitative surveys with students and educators from vocational training centers in Mozambique, the study analyzes different educational approaches and methodologies. It seeks to understand how entrepreneurial education contributes to the development of essential skills such as creativity, innovation, problem-solving, teamwork, and leadership. These skills are increasingly valued by companies demanding professionals who can think critically and adapt to new situations. The research presents experiences from institutions that have implemented entrepreneurial education programs and discusses the observed impacts on student engagement and professional preparedness. The findings indicate that programs which combine theoretical foundations with practical experiences—particularly through active learning strategies and real-world market challenges—effectively foster the development of entrepreneurial thinking and collaborative abilities among students. These approaches enhance engagement, encourage initiative, and help bridge the gap between education and professional practice. The study concludes that integrating entrepreneurial education into vocational curricula is essential to prepare future generations with the critical skills and adaptive mindset needed to succeed in a rapidly evolving global economy.